The Mental Health Effects of Retirement - Jan van Ours; Matteo Picchio (Tinbergen Institute, 2019)
We study the retirement effects on mental health using a fuzzy regression discontinuity design based on the eligibility age to the state pension in the Netherlands. We find that the mental effects are heterogeneous by gender and marital status. Retirement of partnered men positively affects mental health of both themselves and their partners. Single men retiring experience a drop in mental health. Female retirement has hardly any effect on their own mental health or the mental health of their partners. Part of the effects seem to be driven by loneliness after retirement.
Keywords: J26; H55; J14; 330; Retirement; health; regression discontinuity design